The Effect of Islamic Social Reporting (ISR), Leverage and Institutional Ownership on Firm Value and Profitability - Arifin, Syamsul; Yaqin, Abdullah; Dinia, Kur’aini Nur (Jurusan Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Pekalongan, 2020)
This study focuses on knowing the effect of Islamic social reporting (ISR), leverage and institutional ownership on firm value and profitability with the following issues: 1) whether there is an effect of Islamic social reporting on corporate profitability. 2) is there an effect of Islamic social reporting on firm value. 3) whether there is an effect of leverage on corporate profitability. 4) whether there is an effect of leverage on firm value. 5) whether there is an effect of institutional ownership on corporate profitability. 6) whether there is an effect of institutional ownership on firm value. The research is a quantitative study using a population of Sharia commercial banks in Indonesia. This study uses purposive sampling technique which then gets five Sharia commercial banks. The results showed that Islamic social reporting (ISR) has a positive effect on both profitability and firm value. Meanwhile, both institutional ownership and leverage only affect profitability